The Influence of Bead Stringing Play Therapy the Fine Motor Skill of Children with Intellectual Disability - Shinta Dewi; Intan Parulian; Agung Setiyadi; Dyah Agus Triwidyansari (GLOBAL HEALTH SCIENCE GROUP, 2026)
This study examines the use of bead-stringing activities at Soeharto Heerdjan Hospital as a therapeutic intervention for children with intellectual disabilities, whose population continues to increase each year. Bead-stringing has not yet been incorporated into the hospital’s child rehabilitation program, highlighting the need for nurse play specialists to develop innovative therapeutic play approaches. In this study, play therapy was implemented through beading activities, in which children arranged beads or small objects into specific patterns. This activity is intended to stimulate hand–eye coordination and enhance fine motor skills. A quasi-experimental design with pre-test and post-test measurements was used. The sampling technique employed was purposive sampling, involving 36 children aged 5–6 years with mild to moderate intellectual disabilities who actively participated in the Kuas Biru program at the Child and Adolescent Unit of Soeharto Heerdjan Hospital, Jakarta. Fine motor skills were assessed using the Denver II Developmental Screening Test. The Wilcoxon test results showed a significant effect of bead-stringing play therapy on fine motor skills in children with intellectual disabilities, with a p-value of 0.000. The analysis demonstrated an increase in fine motor skill scores, from a pre-test mean of 2.14 to a post-test mean of 3.00. These findings indicate that play therapy using beading activities has a positive impact on improving fine motor skills in children with intellectual disabilities.